PROBLEMS OF CEFR IMPLEMENTATION IN THE EDUCATION SYSTEM OF UZBEKISTAN (Scientific journal of the Fergana State University, 2023)
Thу article is devoted to the history of the CEFR program and how it has been affected to varying degrees as a result of reforms in Uzbekistan in recent years. It discusses the problems that have arisen since the introduction of the CEFR program and their solutions. As a result of the direct introduction of CEFR into the education system, some problems are emerging. This indicates that the CEFR is a relative language program and that each country, each educational institution, must implement it in its own context.